Super-Heróis E Indivíduos Na Contemporaneidade: Dilemas E Anseios Presentes Nas Personagens De Os Vingadores - Martins, Cristiana Domingos [UNIFESP] (2017)
Due To The Prominence And Relevance Of The Superhero Characters In The Current Film Scenario And The Comprehension Of Cinema As A Specific And Privileged Object For Analysis Of The Social World, This Thesis Aims To Analyze The Characters Of The Superhero Group Avengers In Films Produced By Marvel, Such As: Iron Man (2008), The Incredible Hulk (2008) And Captain America: The First Avenger (2011). The Main Goal Of This Research Is To Understand How The Dilemmas And Anxieties Related To Life In The Contemporary Society Are Represented In The Construction Of These Characters, Especially The Dilemmas And Anxieties Related To The Individuals And The Individuality. As Pierre Sorlin Elaborates On Its Proposal To Film Studies, The Preferred Methodology In This Research Is The Internal Analysis Of The Films.